COMPARATIVE ANALYSIS OF MRI, MORPHOLOGICAL AND BIOCHEMICAL FEATURES OF MALIGNANT NEOPLASM OF THE PROSTATE GLAND - Yasnikova, Marharita; Kudriavtsev, Yuriy; Ponyrko, Alina; Malyuk, Anastasiya; Riabenko, Tetiana; Romaniuk, Anatolii (Eastern Ukrainian Medical Journal, 2024)
Introduction. This article presents a comparative analysis of magnetic resonance imaging (MRI), transrectal ultrasound (TRUS), biopsy and biochemical studies in prostate cancer using histomorphologic grading of the tumor component according to the Gleason score. It has been shown that the level of prostate-specific antigen (PSA) often correlated with the total Gleason score.Materials and methods: In the study, 860 patients with suspected prostate cancer were examined: 530 patients (62 %) were diagnosed with prostate cancer at various stages of development, and 330 patients (38 %) were diagnosed with prostate adenoma.MRI of the prostate was performed in three sections: sagittal, frontal and vertical. The tumor component was assessed using the PI-RADS system. Patients with a PSA level of more than 4.4 ng/ml were selected for the study. The stage of cancer development was determined by the Gleason scale during histological examination.Results of own research: It was found that the MRI diagnostic method was most effective in low and moderately differentiated forms of prostate adenocarcinoma and could also be used to assess the prevalence of the tumor process.The first place among the studied cases (61%) was occupied by stage III prostate cancer, the second place – by stage IV prostate cancer (24%) and the third place – by stage II prostate cancer (15%).Hypoechoic nodular elements were detected in 30.2%, mainly 5–7 by the Gleason score, heterogeneous nodular elements – in 40.1% (8 by the Gleason score), hypointense areas, mainly in the peripheral parts of the gland, were detected in 75.2% (9–10 by the Gleason score).Changes in the vascular pattern depended on the degree of development of the tumor component.Conclusion. Our study revealed a number of features: prostate cancer is mainly characterized by highly differentiated and moderately differentiated forms of adenocarcinoma; in metastasized prostate cancer, a low-grade form of adenocarcinoma is more often detected, which can have an aggressive course and rapid spread of the tumor component